VERITAS: Mind-Mapping in Virtual Reality - Sims, Robert; Karnik, Abhijit (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Inquiry based learning is a modern and innovative learning strategy that aims to stimulate students' interest in a topic and target Bloom's higher order cognitive process. Reflective tasks, such as mind mapping, support inquiry-based learning. Virtual Reality (VR) presents novel opportunities to help scaffold reflective tasks in inquiry-based learning by supporting use of the 3D space which is not available via existing 2D mind mapping applications. In this paper we present VERITAS, a VR application for mind-mapping based reflective tasks operating on the low-cost Oculus Go device. We discuss the interaction design for the mind-mapping task and evaluate the system from a usability perspective. Our results show that novice participants are able to learn how to use the interactions quickly and utilize them effectively to build mind-maps in 3D. VERITAS establishes the usability of VR and essential interactions to successfully perform abstract and complex reflective tasks like mind-mapping.